Role of coatings in the formation of defects in advanced high strength steel welds. (2021) - Vijayan, Vijeesh; Ahsan, Md. Rumman Ul; Murugan, Siva Prasad; Park, Yeong-Do
Abstract: Infrared thermography technique (IRT) uses longer wavelength electromagnetic radiations emitted by a hot body to compute its temperature. The radiant energy absorbed by the thermographic system is transformed into electronic signals by sensors and into visible signals known as a thermogram. Besides highly sophisticated military applications, the non-contact infrared thermography is extensively used in medical, electrical, mechanical and many other domains. This paper exploits the infrared thermography technique for precise measurement of temperature across the weld interfaces obtained with two different welding processes, viz. nut projection welding and cold metal transfer gas metal arc welding (CMT-GMAW). The recorded temperature was processed to obtain peak temperature, heat generated, heat affected zones, and to understand the effect of coating on the heat generation and defect formation. IRT results reveal that the weld quality and strength is significantly influenced by the weld pool temperature and region of heat generation in CMT and nut projection welding, respectively.